Rabies virus large protein-derived T-cell immunogen facilitates rapid viral clearance and enhances protection against lethal challenge in mice - Shimeng Bai; Xinghao Pan; Tianhan Yang; Nan Gao; Cuisong Zhu; Ai Xia; Meiqi Feng; Miaomiao Zhang; Xiaoyan Zhang; Jianqing Xu (Communications Medicine)
Abstract Background Rabies remains a devastating and fatal infectious disease worldwide. To date, vaccination is the most reliable and effective strategy for controlling rabies. However, despite the effectiveness of inactivated vaccines, cumbersome vaccination procedures and the high costs of post-exposure prophylaxis impose a significant economic burden, particularly in developing countries with limited access to vaccines. Therefore, there is an urgent need to develop a novel rabies vaccine that reduces costs while enhancing safety and efficacy. Methods We developed a novel mRNA rabies vaccine called RABV-G-LT, which incorporates two immunogens: RABV-G, a glycoprotein designed mainly to elicit neutralizing antibody responses, and RABV-LT, a T-cell immunogen derived from the large protein of the rabies virus. Additionally, we evaluated the immunogenicity of RABV-G-LT in both mice and non-human primates. Results The RABV-LT mRNA vaccination alone induced potent RABV-LT-specific T-cell responses and provided modest protection against rabies virus challenge in mice. Importantly, the dual-immunogen mRNA vaccine RABV-G-LT elicited vigorous and persistent neutralization antibody and T-cell responses, resulting in significantly more efficient clearance of the rabies virus in the brain and spinal cord. This conferred enhanced protection, evidenced by lesser initial weight loss and earlier recovery of body weight compared with the RABV-G mRNA or inactivated vaccine groups. Moreover, RABV-G-LT also mounted persistent strong antigen-specific T-cell and antibody immune responses in nonhuman primates. Conclusions Our study suggested that combining the T-cell immunogen and virus-neutralizing antibody immunogen was a practical approach to strengthening the defense against the rabies virus.